PENENTUAN FREKUENSI RESONANSI PADA ARTIFISIAL METAMATERIAL MENGGUNAKAN BENTUK SPLIT RING RESONATOR (SRR) - Muh Yasin YBIC; K Sofjan Firdausi; Priyono Priyono (Youngster Physics Journal, 2014)
Metamaterial represent the material with negative value of permitivity ( ) and permeability ( ). Artificial metamaterial can be realized with periodic structure of wire for the negative relative permittivity ( ), and Split Ring Resonator (SRR) for the negative relative permeability ( ). This research represent the theoretical study about the dimension effect of SRR to active frequency of electromagnetic wave ( ) at artificial metamaterial. Plasmon resonances in SRR due to the interaction with the electromagnetic waves used to determine  in order to obtain the equation in the form of frequency. From these equations graphically simulated between  to the  at various dimension size of SRR, so can be knowable about the dimension effect of SRR to active frequency of metamaterial. At periodic structure of SRR, if the distance apart of SRR ( ) increase hence top boundary of active frequency (magnetic plasma frequency, ) decrease, and  bottom boundary of active frequency (SRR resonance frequency, ) do not change. If radius of SRR ( ) increase hence will decrease the  and . If  the gap ring of SRR ( ) increase hence increase of  and . Keywords: permitivity, permeability, metamaterial, Split Ring Resonator.